Using Innovative Methods In Club Work - Karimova Dilorom Amonovna (Genius Journals, 2024)
The modern education system requires flexibility in training in order to take into account the specific production requirements for university graduates, as well as for continuing education. The flexibility of educational programs is realized by the introduction of special courses, including extracurricular activities. Extracurricular activities are designed to broaden their horizons and foster students’ creative initiative. One of the main types of extracurricular work is a circle in the specialty and areas of science.
Keywords: main; extracurricular; courses; activities